Left-behind children: teachers' perceptions of family-school relations in rural China. Issue 4 (4th July 2019) - Kim, Sung won
Abstract: Large-scale rural-urban migration in China has left rural schools with large proportions of left-behind children whose parents are away working in the city. This has a huge impact on family-school relations and poses a burden on teachers. This study draws on 42 interviews with teachers working in two rural schools. This article argues that teachers' negative narratives about antagonistic family-school relations are driven by the gaps between their culturally embedded traditional models of family-school relations and the reality, with implications for the expanded role of schools and that of grandparents as caregivers. This article further discusses the implications of these findings for rural schools and draws heavily on Western models of family-school relations in a comparative perspective.